The Influence of APIP Capabilities in Optimizing Financial Audit Efficiency: Optimal Accountability - Muh Ikhsan Bua; Fikry Karim; Megawati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
AbstractThis study aims to analyze the influence of the capabilities of the Government Internal Supervisory Apparatus (APIP) in optimizing the efficiency of financial audits and reducing audit findings to achieve optimal accountability. The study was conducted by collecting annual report documents from the Financial and Development Supervisory Agency (BPKP), the Audit Board of the Republic of Indonesia (BPK), and the Ministry of Home Affairs (Kemendagri). A quantitative approach was used in this study, with data analysis involving 3,252 observations from various government agencies in Indonesia. The data collected included APIP capabilities, financial audit efficiency, and the number of audit findings. The mediating variable used in this study is the follow-up on audit recommendations. The results show that APIP capabilities have a significant impact on the efficiency of financial audits. Increasing APIP capabilities has been proven to significantly enhance audit follow-ups and reduce the number of audit findings. Additionally, the variables of organizational age and geographic factors also significantly affect audit efficiency and the number of audit findings, indicating that these factors are important in achieving better financial accountability. Conversely, the size of the agency negatively affects audit follow-ups and positively affects the number of audit findings. These findings underscore the importance of enhancing APIP competencies and capabilities as a primary strategy in improving the efficiency and accountability of financial audits in the public sector. This study provides significant contributions to the development of internal supervisory policies and the improvement of financial audit quality in Indonesia, as well as encouraging efforts to enhance public sector accountability.Keyword: apip capabilities; financial audit efficiency; audit findings; accountability